Asymmetry response of storm surges along the eastern coast of the Taiwan Strait - Zhang, Ruijie; Shen, Junqiang; Li, Li; Wang, Yuting; Huang, Jiang; Zeng, Mingzhang; Guo, Xiaogang (Frontiers in Marine Science, 2024)
Spatiotemporal variation of storm surges in the Taiwan Strait (TWS) is studied using water-level datasets from fourteen tidal-gauge stations located in the TWS from summer to fall, 2016. The effects of bathymetry on storm surges and tropical cyclone (TC) induced continental shelf wave (CSW) are explored. It's found that storm surges along the eastern coast of TWS are asymmetric on the north and south side of Zhan-Yun Ridge (ZYR), regardless of the different category and track of TCs passing by. Observations indicate that the ZYR could modulate the storm surges and the CSW propagation; ZYR can not only amplify the storm surges which generally peak around the ZYR, but also block the CSW propagation by dramatically dissipating its kinetic energy. Moreover, local wind work and the remote forcing, which are induced by TCs and cold fronts respectively, can also modulate the synoptic variations of water level in TWS.